Kesan senaman aerobik terhadap penanda stres terpilih di kalangan pelajar semasa musim peperiksaan akademik - Farah Fauzi,; Arimii Fitri Mat Ludin,; Mahadir Ahmad,; Kamarul Zaman Maidin, (penerbit ukm, 2006)
Regular physical activities such as aerobic exercise have a good implication in our daily lives especially in the aspects of health and stress management. The aim of this study is to determine the effect of an aerobic exercise program with a selected protocol on selected stress marker levels among university students during academic examination season. Eighteen (n=18) untrained males, matched in age and BMI were divided into two groups i.e intervention (n=10) and control(n=8) groups. The intervention group underwent an aerobic exercise program of moderate intensity (60-75% of maximum heart rate), thrice weekly, 40-50 minutes per session for 6 weeks. Venous blood was collected before the commencement of the exercise program (M1) and post-program six weeks later (M2), during the first week of the examination season. Biochemical analyses were carried out for the determination of plasma malondealdehyde (MDA) and serum cortisol. Cardiorespiratory fitness and psychological status were assessed prior to both blood sampling sessions. The 6-week intervention exercise induced a significant decrease in MDA levels during examination period as compared to that measured before the exercise program (F=19.58, p=0.002). The intervention group also showed significantly lower MDA levels than that of control group during the examination period (t=-0.42, p=0.001). However there were no significant differences noted in cortisol levels in both groups although a slight decrease was observed in the intervention group during examination period. These findings suggest that the exercise program might be an effective coping strategy for students when dealing with stress especially during academic demanding times.